Current Trends of Immune System Engineering in Healthcare Applications - K.Vivekanandan (Recent Research Reviews Journal, 2022)
Immune system engineering presents significant challenges as well as great opportunities for biomedical engineers. Human immunity is critical to both health and disease, and immune system activation plays a critical role in disease prevention. The malfunctioning of the human immune system will result in autoimmune disorders, cardiovascular disease, cancer, and other serious diseases. Immune engineering responds to the immune system's complex challenges by targeting a variety of cellular and molecular processes, such as improving antigen presentation, reviving worn-out tumour cells, engineering immune effectors and cells, and improving drug delivery to targeted immune tissues or cells. By reprogramming specific biological responses and developing technologies for early disease detection, numerous opportunities will emerge to boost the human immune system while keeping costs under control. This article discusses about the current trend of using immune engineering in healthcare.
Keywords: Immuno-engineering; immune system; biomedical engineers; tumor cells; immune response